Correlation of Serum Decoy Receptor 3 and Interleukin-6 with Severity of Coronary Artery Diseases in Male Acute Myocardial Infarction Patients: DcR3 in myocardial infarction - Doustkami, Hossein; Avesta, Leli; Babapour, Behzad; Boskabady, Mohammad Hossein; Nikoukhesal, Ali; Aslani, Mohammad Reza (Acta Biomedica Atenei Parmensis, 2021)
Background: Decoy receptor 3 (DcR3), is a soluble receptor which is thought to have immune modulator or pro-inflammatory effects. Various risk factors have been suggested for the incidence of cardiovascular diseases (CADs) such as an increase in inflammatory factors. The purpose of the present study was to investigate the correlation of DcR3 with anthropometric, angiographic, echocardiographic, and biochemical parameters in patients with acute myocardial infarction. Methods and Materials: A total of 90 patients who were candidates for angiography were included in the study and were divided into three groups: 30 patients with acute myocardial infarction (AMI), 30 patients with stable angina pectoris (SAP), and 30 subjects as control group with a history of chest pain but normal angiography. Anthropometric, angiographic, echocardiographic, and biochemical parameters were measured in all subjects. Results: Serum DcR3 and interleukin (IL)-6 levels were significantly increased in patients with AMI compared with SAP and control groups (P < 0.05 to P < 0.001). In addition, there was a positive association between serum level of DcR3 and epicardial fat thickness (EFT), Gensini score, creatine kinase (CK)-MB, IL-6, and white blood cell (WBC) count in CAD patients. The results of multivariate linear regression analysis revealed that WBC count and IL-6 levels were independently associated with serum DcR3 levels. Conclusion: The current study showed an association of DcR3 and IL-6, WBC count, EFT, CK-MB, and Gensini score for the first time in male AMI patients. Increased DcR3 levels in patients with AMI may be involved in the process of atherosclerosis.